2023
DOI: 10.1055/a-2101-9533
|View full text |Cite
|
Sign up to set email alerts
|

Horse allergy: Curly Horses can mediate immune tolerance

Alexandra Mitlehner,
Caspar Mitlehner,
Monika Reißmann
et al.

Abstract: American Bashkir Curly Horses are claimed to be hypoallergenic, but this has not been clinically proven. In the present study, the effect of exposure to Curly Horses was investigated in 141 patients allergic to horses by measuring their lung function and nasal patency during Curly Horse contact. Continuous contact with Curly Horses, including riding and brushing, decreased the allergic ridersʼ reactivity as measured by FEV1, PEF, and PNIF. Subsequent visits (up to 40 or more hours of riding) further reduced re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A clinical study enrolling 41 patients with horse allergy to a tolerance induction protocol including regular riding 1 of 4 Curly Horses (treatment group, n = 27) found that 12 out of 12 participants of the treatment group who completed the study had a negative NPT [ 30 ]. However, a total of 15 participants in the treatment group withdraw before the end of the study and 12 of those had a positive NPT.…”
Section: Allergens Of Furry Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical study enrolling 41 patients with horse allergy to a tolerance induction protocol including regular riding 1 of 4 Curly Horses (treatment group, n = 27) found that 12 out of 12 participants of the treatment group who completed the study had a negative NPT [ 30 ]. However, a total of 15 participants in the treatment group withdraw before the end of the study and 12 of those had a positive NPT.…”
Section: Allergens Of Furry Animalsmentioning
confidence: 99%
“…An important drawback of the study is that it only included a control group of patients with low exposure to Curly Horse (n = 14; < 7 riding hours/year), but no control group exposed to non-Curly horse riding. Notably, patients who had longer periods of riding (> 20 hours) and whose symptoms disappeared, initially had mild symptoms [ 30 ]. In order to provide scientific evidence of the Curly Horse to be hypoallergenic, a broader clinical study involving a treatment group and a control group riding non-Curly horses has to be designed, including a categorization by symptom scores and IgE profiling of patients as well as a determination of allergen content of the horses those patients are exposed to.…”
Section: Allergens Of Furry Animalsmentioning
confidence: 99%